Media research in the Arab world, its current reality and potential for its development - GHARAM, Djihad; BELDJOUHAR, Khaled (Social Sciences Journal)
The role of media research in rationalizing the communication policies involved in functions, means, and methods is considered a qualitative new field that requires awareness and awareness of the complex nature of the media phenomenon, and the need to rely on different and varied sciences, specializations, and experiences to understand it. However, there is severe disregard in our Arab world for this. The aspect and superficial view of the role of media research in crisis management at its various levels, and assigning the tasks and functions of media practices in various institutions to non-specialists, or to some successful and distinguished media and public relations men in their performance in normal situations, but they may not be so in dealing with crises. Mobilizing public opinion in its direction, because the situation of the crisis calls for a different quality of media coverage and treatments, as well as a special type of media activities that go beyond official statements and discourses that cannot play their role in the face of the free flow of opinions and information, and the plurality of choice of recipients offered by the globalization of media.